Pengaruh Layanan Konseling Kelompok terhadap Self-Efficacy Siswa yang Mengalami Kesulitan Belajar - I Wayan Dharmayana; Meita Pratami (Universitas Mathla'ul Anwar Banten, 2019)
THE EFFECT OF GROUP COUNSELING SERVICES ON SELF-EFFICACY OF THE STUDENT WITH LEARNING DIFFICULTIES. A student with learning difficulties tends to have low self-efficacy in the learning process. The student should be encouraged to have high self-efficacy. Higher self-efficacy shows a more persistent attitude, engage in learning, not worry, and not experience pressure in dealing with problems. This study aims to describe the effect of group counseling services on the self-efficacy of students with learning difficulties in students in Junior High School. This research is a quasi-experimental with one group pre-test-post-test design. The subjects of this were eight students in class VIII. Data collected by AUM PTSDL to found the student with a Learning difficulty and self-efficacy questionnaires to measure the self-efficacy of the student. The results showed that the students' self-efficacy in learning difficulties increased after treatment with the group counseling service. It has shown from the results of differences test between pretest and postest with Wilcoxon Signed Rank Test (Z test) value = -2, 527 (p < 0,05). This means that there was a significant differences self-efficacy of students with learning difficulties before and after group counseling services treatment to the subject. Self-efficacy of the student increase after treatment. This result then was discussed.